Fabrication of Rice Husk Through Compaction Techniques for Water Filter Application - James, Jemima Fae; Ahmad, Sufizar; Nurul Ain Shuhada Othman; Siti Sarah Sofia Mustpha@Mustapha (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Rice husk are the outermost protective layer of rice grains. It is a byproduct that is usually removed during the rice milling process. Disposing of rice husks, frequently regarded as agriculture waste, poses environmental problems. Nevertheless, these have drawn attention because of their potential uses in various industries. The compaction method applied to rice husk has revolutionized its utility, transforming this once-discarded agriculture waste into a valuable resource. Their energy density is significantly increased by crushing and compressing rice husks into denser forms such as briquettes or pallets, making them more efficient for transportation, storage and application. This paper discusses fabrication of rice husk through compaction techniques for water filter application. Since silica is the main material, it must be treated carefully as it might harm the environment. The mixture of the sample contains 65:17.5;17.5 ratios by weight of rice husks silica, water and polyethylene glycol. The silica compositions of water filters is adjusted to 65wt%, 70wt%, 75wt%, 80wt% and 85wt%. Then, the sample of water filter go through the sintering process at a temperature of 1200 degree celcius. Porosity and density testing were performed to see physical properties of the water filter samples. The analysis performed is microstructural analysis. The results show that 65wt% composition has the highest apparent porosity of 47.34%, indicating a larger volume fraction of open pores within the material, while 85wt% composition has the lowest apparent porosity of 39.77%. For the density, 85wt% composition has the highest density of 1.37g/cm3, while 65wt% composition has the lowest density of 1.28 g/cm3 . In conclusion earlier chapter prove that the research has achieved its goal. The study’s main goal is to produce silica from rice husk ash. Then it successfully produced samples of different compositions using the compaction method and perform the physical testing.